2010
DOI: 10.1007/s11104-009-0269-6
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition and nutrient dynamics in mixed litter of Mediterranean species

Abstract: In the last decade a great research effort addressed the effects of litter diversity on ecosystem functions, reporting both synergistic and antagonistic effects for decomposition dynamics. Four coexisting Mediterranean species, representing a range of litter quality, were used to arrange litter mixtures at three diversity levels for a litterbag decomposition experiment. Species identity appeared as the major determinant for litter mass loss (Coronilla emerus∼Hedera helix>Festuca drymeia>Quercus ilex) and nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
4
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 57 publications
7
66
4
3
Order By: Relevance
“…We could observe more physical breakdown of the Mongolian oak leaf litter in the mixed leaf litter. However, contrary to our expectations that transport of nutrients between the Mongolian oak leaf litter and the Korean pine leaf litter would induce complementary interactions and a synergistic effect, an actual mixed effect on the remaining mass was not detected within 24 months, suggesting that synergistic effects of mixed leaf litters of contrasting qualities is questionable [29,43]. Moreover, the seasonal climate was a primary control on the leaf litter decomposition pattern, making species difference less powerful in leaf litter decomposition in a temperate deciduous forest [44].…”
Section: Mixed Leaf Litter Effectcontrasting
confidence: 99%
See 2 more Smart Citations
“…We could observe more physical breakdown of the Mongolian oak leaf litter in the mixed leaf litter. However, contrary to our expectations that transport of nutrients between the Mongolian oak leaf litter and the Korean pine leaf litter would induce complementary interactions and a synergistic effect, an actual mixed effect on the remaining mass was not detected within 24 months, suggesting that synergistic effects of mixed leaf litters of contrasting qualities is questionable [29,43]. Moreover, the seasonal climate was a primary control on the leaf litter decomposition pattern, making species difference less powerful in leaf litter decomposition in a temperate deciduous forest [44].…”
Section: Mixed Leaf Litter Effectcontrasting
confidence: 99%
“…The predicted remaining mass for the mixed leaf litter was estimated using equation (3) based on the observed remaining mass of the single species to verify a mixed effect on leaf litter decomposition [29]. The predicted results were compared with the observed remaining mass of the mixed leaf litter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Berg and McClaugherty (2013) suggested that the use of C/N ratio to predict decay rate throughout the decomposition process should be avoided, because, irrespectively of its initial value, it progressively decreases as C is lost trough respiration, while N is immobilized in the microbial biomass (Bonanomi et al 2010). More recently, Hättenschwiler et al (2011) revisited the commonly held view that N and lignin control the rate of plant litter decomposition, and indicated that, at least in tropical ecosystems, non-lignin plant carbon molecules at low concentration play the major role.…”
Section: Originalmentioning
confidence: 99%
“…Phenolic compounds present in the soil determine both the rate of decomposition of post-harvest residues and the release of nutrients therefrom. In monocultural crop cultivation the accumulation of soil humus may be slowed down due to the impact of phenolic antimicrobial substances, which include, inter alia, tannins and polyphenols (Wardle et al 2003, Bonanomi et al 2010. Both the quantitative and qualitative compositions of phenolic compounds in the soil are, to a large extent, dependent on the vegetation and soil (Mala et al 2013, Natywa et al 2014).…”
Section: Introductionmentioning
confidence: 99%